P217 Prevalence of COVID-19 in IBD patients treated with infliximab and vedolizumab in Croatian tertiary center – clinical observation of a case series. (21st January 2022) - Domislović, V; Brinar, M; Čukovic-Čavka, S; Turk, N; Grgić, D; Barišić, A; Jelaković, M; Krznarić, Ž
Abstract: Background: The risk of COVID-19 in patients with IBD is considered comparable to general population. However, it has been hypothesized that patients on immunosuppressive therapy could be more susceptible to SARS-CoV-2, mainly due to well-known association of immunosuppressive therapy and increased risk of viral infections. Our aim was to examine the frequency of COVID-19 infection among tertiary center IBD patients treated with biological therapy. Methods: These are descriptive data including IBD patients on biological therapy which are regularly followed in Croatian referral IBD center at the University Hospital Centre Zagreb, Croatia. Patients on adalimumab were excluded since they are not regularly followed and are receiving therapy at home. SARS-CoV-2 infection was identified as RNA positive nasopharyngeal swab. Disease activity was measured using Harvey-Bradshaw Index (HBI) in CD, partial Mayo score (pMayo) in UC, and CRP. COVID-19 was defined as mild as any of the symptoms consistent with COVID-19 without shortness of breath, dyspnea, abnormal chest imaging and room SpO2>=97%. Results: Out of total 234 patients on infliximab 15 (6.4%) had COVID-19, which was the case for 3 out of 48 (6.2%) patients on vedolizumab. We have not documented COVID-19 among 67 patients on ustekinumab and 10 on golimumab. Among infected there were 9 patients with CD, 8 UC and 1 IBD unclassified, 61.1% were male and average age was 37 (SD 12). All patients had mild clinical picture with symptoms lasting around 3 days. Overall, 3 UC patients on infliximab had worsening of IBD symptoms (bloody stools and diarrhea) in approximate time to and after COVID infection (increase of pMayo by >=2 points) with only 1 patient requiring glucocorticoid therapy. One male patient had prolonged post-COVID syndrome in terms of fatigue and mild dyspnea over 4 months, but suffered from bronchial asthma. There was no difference in HB index, pMayo or CRP before and after COVID-19 infection (p>0.05). Loss of smell and taste was present 3 patients. Conclusion: Our analysis was limited to IBD patients scheduled to receive a visit; hence it could not represent general IBD population. However, according to the results of other studies, we did not gain the impression of increased risk of infection or poorer clinical outcome in IBD patients on biological therapy. In addition, study from Singh AK et al. reported worse outcomes of COVID-19 IBD patients in UC, but not on biological therapy, which is also in line with our observation (1). Reference: 1. Singh AK et al. Risk and outcomes of coronavirus disease in patients with inflammatory bowel disease: A systematic review and meta-analysis. United European Gastroenterol J. 2021;9:159–176.